Analysis of Risk Factors Affecting the Incidence of Covid-19 in Nurses at Dr. Rsup. Moh Hoesin (Rsmh) Palembang - Yuliana Kumaladewi; Rahmiati (Jurnal RSMH Palembang, 2021)
As many as 59% of nurses work on the front lines during the covid-19 pandemic which is the largest proportion of health workers (WHO, 2020) Starting from the beginning of the pandemic until March 2021, 147 nurses in RSMH have been exposed to covid-19 (31.21%) and until now incidence is still high. The purpose of this study was to identify risk factors that influence the transmission of covid-19 in nurses at RSMH Palembang. The dependent variable was covid-19 incident on nurses and the independent variable were age, gender, work experience, work area, distance-keeping behavior and compliance with wearing PPE. This research used an analytic observation design with a retrospective cohort approach on 1196 nurses who participated in the RSMH covid-19 screening during the period March 2020-March 2021. The sample selection was carried out using a consecutive sampling technique and 1131 samples were obtained that met the inclusion criteria. Covid-19 occurred in 87 nurses (7.7%). The results of the bivariate test showed that there was an effect of gender (p=0.023), work area (p=0.026) and adherence to wearing PPE (p=0.001) on the incidence of Covid-19 in nurses. The results of the logistic regression test show that compliance with wearing PPE is the most influential factor on covid-19 with a probability of 87.92%. Hospitals must pay more attention to nurses who are at risk of being exposed to COVID-19, namely nurses who are male and work in red zone areas. Guaranteeing the availability of PPE and monitoring and evaluation of PPE compliance must be routinely carried out by hospital management.